2022
DOI: 10.1002/ame2.12297
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing peripheral circulating IL1β slows the progression of ALS in a lentivirus‐infected OPTNE478G mouse model

Abstract: Background: Amyotrophic lateral sclerosis (ALS) is irreversible and fatal within 3-5 years, with limited options for treatment. It is imperative to develop a symptombased treatment that may increase the survival of ALS patients and improve their quality of life. Inflammation status, especially elevated interleukin 1β (IL1β), has been reported to play a critical role in ALS progression. Our study determined that neutralizing circulating IL1β slows down the progression of ALS in an ALS mouse model. Methods: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…Unfortunately, there is currently little research into the treatment of ALS due to OPTN deficiency. One study found that neutralizing peripheral circulating IL1β could regulate neuroinflammation and improve motor function in OPTNE478G mouse model ( Hu et al, 2023 ). Another study also found that blocking RIPK1 may provide a treatment option for OPTN mutation-mediated ALS by inhibiting axonal degeneration caused by inflammation and necroptosis ( Ito et al, 2016 ).…”
Section: Foresightmentioning
confidence: 99%
“…Unfortunately, there is currently little research into the treatment of ALS due to OPTN deficiency. One study found that neutralizing peripheral circulating IL1β could regulate neuroinflammation and improve motor function in OPTNE478G mouse model ( Hu et al, 2023 ). Another study also found that blocking RIPK1 may provide a treatment option for OPTN mutation-mediated ALS by inhibiting axonal degeneration caused by inflammation and necroptosis ( Ito et al, 2016 ).…”
Section: Foresightmentioning
confidence: 99%
“…Elle perturbe également le recrutement de l'OPTN aux chaînes d'ubiquitine et inhibe la mitophagie[36]. D'un point de vue clinique, l'utilisation d'anti-IL-1b améliore la symptomatologie de souris transgénique OPTN-E478G[37]. L'expression chez la souris d'une mutation (OPTN-470T5 ), qui inhibe également la liaison aux ubiquitine, n'a pas permis d'observer de neurodégénerescence, que ce soit chez la souris jeune ou âgée[38].…”
unclassified